Synergistic effect of enteral nutrition on remission induction in a patient with penetrating Crohn disease: A case report. Issue 32 (August 2019) - Xie, Chenxi; Lin, Jinzhou; Su, Jingling; Ren, Jianlin
Abstract: Rationale: Crohn disease includes 3 phenotypes, inflammatory, stricturing, and penetrating. In cases where corticosteroids and immunosuppressive agents are not suitable treatment options, enteral nutrition (EN) can be used to reduce disease severity and enhance barrier defense with fewer potential adverse effects. Patient concerns: A 23-year-old man with abdominal pain and diarrhea presented at our hospital in 2014. The frequency of defecation was 3 or 4 times a day without mucus or blood in the stool. His body mass index was 15.8, and in laboratory tests the erythrocyte sedimentation rate was 42.4 mm/h, serum C reactive protein was 65.2 mg/L, the leukocyte count was 11.64 × 109/L, and hemoglobin was 111 g/L. Diagnosis: In computed tomography (CT) enterography the ascending colon was thickened, and there was effusion and enlarged lymph nodes around the colon. Colonoscopy revealed ulcer, polypoid proliferation, and bowel stenosis in many segments. Chronic inflammation was evident in multiple biopsies. Crohn disease was diagnosed based on the above observations. Interventions: Mesalazine was administered at a dose of 4 g daily for 2 years. The patient was hospitalized again due to severe abdominal pain and ongoing fever. Intestinal perforation was detected via CT. Percutaneous drainage was performed followed by administration of intravenous metronidazole (0.5 g) and ciprofloxacin (0.2 g) twice a day. Peptison liquid was used as exclusive EN. After 2 weeks the antibiotics regimen was changed to metronidazole 0.4 g twice a day and ciprofloxacin 0.25 g 3 times a day, both administered orally. Outcomes: CT revealed that the infection was eliminated and the fistula was healed after 10 weeks, at which point antibiotics and exclusive EN was discontinued. Azathioprine was prescribed at a dose of 2 mg/kg daily to maintain clinical remission. The patient did not report any pain or diarrhea at a 1-year follow-up visit. Lessons: The present case suggests that exclusive EN combined with antibiotics is useful in inducing remission in Crohn disease patients with active disease and penetrating complications.